(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This article is an account of the author ’s experience as a student of the Reduced Model Workshop: Maquete-objeto: ‘maquetes de um mundo imaginário’ taught by Professor Doris Rollemberg in the special academic period of 2020.1 within the scope of the undergraduate course in Scenography at the Unirio Theater School. This report analyzes both the creative process behind the work carried out as well as the resulting textual (creative confessions), two-dimensional (sketches), three-dimensional (models) and four-dimensional (artist book) products that were developed during the course by the author.